Proceedings of the 12th Participatory Design Conference: Exploratory Papers, Workshop Descriptions, Industry Cases - Volume 2 2012
DOI: 10.1145/2348144.2348164
|View full text |Cite
|
Sign up to set email alerts
|

User participation in implementation

Abstract: Systems development has been claimed to benefit from user participation, yet user participation in implementation activities may be more common and is a growing focus of participatory-design work. We investigate the effect of the extensive user participation in the implementation of a clinical system by empirically analyzing how management, participating staff, and non-participating staff view the implementation process with respect to areas that have previously been linked to user participation such as system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This focus on implementation of the new technology as part of PD also therefore raises the notion of user participation in that implementation process. Fleron et al (2012) demonstrated this in the context of first designing an electronic whiteboard with healthcare practitioners, followed by healthcare practitioner-led implementation of that whiteboard at two emergency departments. Notably, this work investigated differences in the experiences between staff who did and did not participate in this implementation process.…”
Section: Related Workmentioning
confidence: 99%
“…This focus on implementation of the new technology as part of PD also therefore raises the notion of user participation in that implementation process. Fleron et al (2012) demonstrated this in the context of first designing an electronic whiteboard with healthcare practitioners, followed by healthcare practitioner-led implementation of that whiteboard at two emergency departments. Notably, this work investigated differences in the experiences between staff who did and did not participate in this implementation process.…”
Section: Related Workmentioning
confidence: 99%
“…All of those that were involved with the forms (whether answering, administering, or analyzing the forms) were involved in the process. Others have found collaboration among different levels improves buy-in (11), and that improvements in data collection can bene t different groups of people (12).…”
Section: Settingmentioning
confidence: 99%